2013
DOI: 10.1002/ece3.819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inbreeding on fitness‐related traits in a small isolated moose population

Abstract: Inbreeding can affect fitness-related traits at different life history stages and may interact with environmental variation to induce even larger effects. We used genetic parentage assignment based on 22 microsatellite loci to determine a 25 year long pedigree for a newly established island population of moose with 20–40 reproducing individuals annually. We used the pedigree to calculate individual inbreeding coefficients and examined for effects of individual inbreeding (f) and heterozygosity on fitness-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 87 publications
(221 reference statements)
0
39
0
Order By: Relevance
“…Fitness of Vega moose is negatively related to parental relatedness [15], as is common in wild populations [3], suggesting that inbreeding avoidance is beneficial and expected to occur if allowed by the population structure. We found that the probability for realization of potential mating events was negatively associated with parental relatedness, but the strength of the relationship was affected by the number of males available for mating (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Fitness of Vega moose is negatively related to parental relatedness [15], as is common in wild populations [3], suggesting that inbreeding avoidance is beneficial and expected to occur if allowed by the population structure. We found that the probability for realization of potential mating events was negatively associated with parental relatedness, but the strength of the relationship was affected by the number of males available for mating (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the island Vega (paper III, see Fig. 1) the population of moose has a history which has been tracked back to one male and two female yearling immigrants which founded the population in 1985 Haanes et al, 2013). Several immigrants to the population has been recorded since and a few moose has emigrated Herfindal et al, 2014).…”
Section: The Moose Study Systemmentioning
confidence: 99%
“…This has kept the winter population size around 25 to 43 individuals annually . Using tissue samples from harvested and marked individuals, a genetic pedigree had been constructed with a total of 499 individuals born in the period 1984-2012 (Haanes et al, 2013).…”
Section: The Moose Study Systemmentioning
confidence: 99%
See 2 more Smart Citations